Strenhgtening of masonry infill walls under out-of-plane loading with textile reinforced mortar (TRM) - Martins, Andreia (2014)
The vulnerability of masonry infill walls has been highlighted in the recent earthquakes, in which severe in-plane damage and ou-of-plane collapse developed, justifying the investment in the proposal of strengthening solution aiming at improving the seismic performance. Therefore, this work presents a possible innovative solution to be applied on masonry infill walls, in order to avoid brittle failure and thus minimize the material damage and human losses. The textile reinforced mortar technique (TRM) has shown to improve the out-of-plane resistance of masonry and clearly to enhance its ductility. An innovative reinforcing mesh composed of braided composite rods is proposed with particular characteristics, including the ability to be designed in terms of mechanical requirements at low cost and low technology production. The developed meshes were compared with commercial solutions with the same mechanical characteristics.